(3OjhGf GdeJfHjs - (3CHh GdWjH, GdeJfHj, CMeO Hf GdMSjf Hf GdMSf, J(B354(3g`s
(3ChdgG (B:s
(3GdMH eG efY GdcdGe GdCdSfG (B*** (3hCdP Tchi YGTb eG CYdfG , djJ GdMHjH GdgGLQj gLQ GdcQG (B*** (3ef ZjQ LQe hCUdi Udg GdUfGs
(3BNQgG (B:s
(3CbGVjfG gPG GdPj CfJ Cgdg (B*** (3ZdWJ hdG GdKdKGf gPG hdG Cda GdfUa , PfHj JbUjQj heG LHJ eGOMG (B*** (3HPfHj hdcf LFJ CSCd Cf JYahGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 115s
(3eYLe GdeDdajf(B: 1 / 126s
(3cTa GdXfhf(B: 1 / 809s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs